Patrones de consumo de alcohol en una población femenina de estudiantes de enfermería - Iglesias López, Mª Teresa; Mata, G; Renghea, A; Pavanello, C (Nutrición Clínica y Dietética Hospitalaria, 2020)
Youth alcohol consumption as a public health problem. Objective: To describe the patterns of alcohol consumption among nursing students. Methodology: descriptive, cross-sectional study, 433, university students, undergraduate nursing course, Spain; 2015- 2016, application of the AUDIT questionnaire and some questions from SIVFRENT-A, SPSS analysis. Results: 100% women, average age 21 years, 77.6% consumed alcohol in the last 12 months; 62.1% in the previous 30 days and 9.3% consumed it daily, 55.6% started drinking between 15 and 17 years. Conclusion: it is possible to describe and understand the behavior of nursing students regarding alcohol consumption, clearly addressing the issues in the scarcity of basic education for the prevention of excessive drinking and the strengthening of responsible drinking, reflected in the early onset of drinking. alcohol, a risk factor for excessive alcohol consumption in adulthood and future professional difficulties.